eLearning to facilitate the education and implementation of The Chelsea Critical Care Physical Assessment: a novel measure of function in critical illness. - Corner,E; Handy,JM; Brett,SJ (BMJ Open, 2016)
Objective: To evaluate the efficacy of eLearning in the widespread standardized teaching,distribution and implementation of The Chelsea Critical Care Physical Assessment tool (CPAx): avalidated tool to assess physical function in critically ill patients.Design: Prospective educational study. An eLearning module was developed through aconceptual framework, using the four-stage technique for skills teaching to teach clinicians howto use the CPAx. Example and test video case studies of CPAx assessments were embeddedwithin the module. The CPAx scores for the test case studies and demographic data wererecorded in a secure area of the website. Data were analyzed for inter-rater reliability usingintraclass correlation coefficients (ICC) to see if an eLearning educational package facilitatedconsistent use of the tool. A utility and content validity questionnaire was distributed after oneyear to eLearning module registrants (n= 971). This was to evaluate uptake of the CPAx inclinical practice and content validity of the CPAx from the perspective of clinical users.Setting: The module was distributed for use via professional forums (n=2) and direct contacts(n=95)Participants: Critical care cliniciansPrimary outcome measure: Intraclass correlation co-efficient of the test case studies.Results: Between July and October 2014, 421 candidates from fifteen countries registered forthe eLearning module. The ICC for case one was 0.996 (95% CI 0.990-0.999; n=207). The ICC for case two was .988 (0.996-1.000; n=184). The CPAx has a strong total scale content validityindex (s-CVI) of 0.94 and is well utilized.Conclusions: eLearning is a useful and reliable way of teaching psychomotor skills, such as theCPAx. The CPAx is a well-utilized measure with high content validity rated by clinicians.